English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-01-27 13:11:17 · 11 answers · asked by wiggafree 1 in Science & Mathematics Mathematics

11 answers

subt y for the second equation

x+3(2x-1)=11
x+6x-3=11
7x=14
x= 2

y= 2(2)-1
y= 3

(2,3)

2007-01-27 13:15:17 · answer #1 · answered by      7 · 0 0

2

2007-01-27 21:15:11 · answer #2 · answered by Pete aka arab_uk 1 · 0 1

X+3(2x-1)=11 Plug in what you do know y=2x-1
x+6x-3=11 Multiply your 3 through your ()
7x-3=11
7x=14 Get your like term together on each side
x=14/7 You divide both sides by 7 leaving a 1 in front of the x
x=2

2007-01-27 21:39:26 · answer #3 · answered by ash 1 · 0 0

if this is a set of equations that you work with together, then what you do is:

first, since y=2x-1, substitute that into y in x+3y=11. so you would have x+3(2x-1)=11. now, you can solve for x, since there is only one variable to work with now. u should get x+6x-3=11, then 7x-3=11, then 7x=14, so x=2. now that you have x, substitute it into the first equation. so, y=2(2)-1, then y=3.
so x=2, y=3. and there you are.

2007-01-27 21:20:33 · answer #4 · answered by moofieskoofie411 1 · 0 1

First: replace "2x-1" with the y-variable in the 2nd equation...

x + 3(2x - 1) = 11

*Eliminate parenthesis - use distribution > multiply the outer term with the terms in parenthesis...

x + 3(2x) + 3(-1) = 11
x + 6x - 3 = 11

*Combine "like" terms...

7x - 3 = 11

Sec: add "3" to both sides...

7x - 3 + 3 = 11 + 3
7x = 14

*Isolate "x" on one side > divide both terms by "7"...

7x/7 = 14/7
x = 2

Third: replace "2" with the x-variable in the 1st equation...

y = 2(2) - 1
y = 4 - 1
y = 3

Solution: (2,3)

2007-01-27 23:47:06 · answer #5 · answered by ♪♥Annie♥♪ 6 · 0 0

y=2x-1 thus

x + 3(2x-1) = 11
x + 6x - 3 = 11
7x = 11 + 3
7x = 14
x = 14/7
x = 2

y = 2x - 1
y = 2(2) - 1
y = 4 - 1
y = 3

2007-01-27 21:22:36 · answer #6 · answered by zirconiag 5 · 0 0

Multiply the second equation by -2.
Cancel out the -2x and 2x from both equations.
Then solve for y. And solve for x using any of the equations.

2007-01-27 21:16:21 · answer #7 · answered by Anonymous · 0 1

y=2x-1
3y=-x+11

I would multiply the second equation by 2 and then add the two equations to get

y=2x-1
6y=-2x+22
---------------
7y = 21 ==> y = 3

3=2x-1 ==> x = 2

2007-01-27 21:19:26 · answer #8 · answered by Dennis H 4 · 0 0

x=2
y=3

2007-01-27 21:16:40 · answer #9 · answered by karthick k 1 · 0 0

x= 2
Y= 3

2007-01-27 21:18:00 · answer #10 · answered by mazo 1 · 0 0

fedest.com, questions and answers